ASSESSMENT OF MICROPLASMA SPRAYING OF BIOACTIVE COATINGS ON TITANIUM IMPLANTS FOR BIOCOMPATIBILITY IN VITRO - Nwachukwu, China Jesse (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This study presents an assessment of microplasma spraying (MPS) as a technique for applying bioactive coatings on titanium implants to enhance biocompatibility in vitro. The research aims to evaluate the effectiveness of MPS in promoting osteogenic differentiation and antimicrobial activity of titanium implants through in vitro assays. Surface-modified titanium implants with zirconium, hydroxyapatite, tantalum, and titanium coatings of varying roughness were fabricated using MPS. Osteogenic differentiation potential was assessed via alkaline phosphatase (ALP) activity and alizarin red staining, revealing significant variations in mineralization among the different coatings. Antimicrobial studies utilizing Escherichia coli as a model organism demonstrated differential growth kinetics in the presence of implant material extracts, suggesting potential antimicrobial properties associated with specific coatings. The results underscore the importance of surface modifications in influencing osteogenic differentiation and antimicrobial activity of titanium implants. Zirconium, hydroxyapatite, and tantalum coatings exhibited distinct mineralization patterns and antimicrobial effects compared to uncoated titanium, highlighting the potential of MPS in enhancing the biocompatibility of titanium implants. These findings contribute to the understanding of surface engineering techniques for implant materials and pave the way for further research aimed at optimizing coating formulations and deposition parameters to improve implant performance and clinical outcomes
Keywords: type of access: restricted access